Indonesian EFL Pre-Service Teachers’ Challenges and Solutions in Distance Learning Context - Syaniah, Azmi Ellah; Fithriani, Rahmah (Graduate Program Magister Manajemen Pendidikan, 2023)
Since the Covid-19 phenomenon until the present, distance learning has become a common learning method. This learning method makes participation in the learning activity easier and more superficial for students, as the activity can be completed anywhere via online platforms and devices such as laptops and smartphones. However, many students still face obstacles when learning through this mode, which necessitates the development of solutions. While research on the challenges and solutions of distance learning from the perspective of general students has been conducted, little has been conducted from the perspective of Indonesian EFL pre-service teachers. This study, thus aimed to examine the distance learning challenges and solutions encountered by 10 Indonesian EFL pre-service teachers who were invited to be the participants of this study through a purposive sampling technique. The results show that the EFL pre-service teachers face four major challenges in distance learning, namely: network, platform, instruction and interaction, and boredom. As they must engage in distance learning activities, they must implement solutions to the associated difficulties. The solutions are finding a location with a good and stable internet connection, utilizing Wi-Fi, and preparing a backup of internet data, self-teaching or consulting with peers to master the application's functionality, asking the instructors in groups or individually, and being self-motivated. This study suggests that the government, educators, and parents must assist them.